2019
DOI: 10.1007/978-3-030-30000-5_44
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Manufacturing: A Classification of Elements Enabling Convertibility and Scalability

Abstract: Reconfigurable manufacturing, providing capacity and functionality on demand, is an ever more important factor of competitiveness in volatile, unpredictable , and rapidly changing markets. In this regard, scalability and convertibil-ity are considered particularly relevant characteristics, as they directly reduce re-configuration effort and enhance system responsiveness. However, in previous research, scalability and convertibility have predominately been addressed conceptually on a high level of abstraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…We suggest that for a specific application in a company, the abstraction level of the concept is reduced by identifying and selecting the available and relevant technical solutions within each module. This leads to a specification of the modules and provides a more tailored, transparent solution [10].…”
Section: Fig 2 Concept Sections and Corresponding Modulesmentioning
confidence: 99%
“…We suggest that for a specific application in a company, the abstraction level of the concept is reduced by identifying and selecting the available and relevant technical solutions within each module. This leads to a specification of the modules and provides a more tailored, transparent solution [10].…”
Section: Fig 2 Concept Sections and Corresponding Modulesmentioning
confidence: 99%
“…Among the 6 characteristics, scalability and convertibility are those directly related to manufacturing systems' responsiveness to sudden changes: scalability to changes in demand and convertibility to changes in product mix [13]. Indeed, scalability and convertibility directly contribute to the goal of the reconfigurable systems, which is providing exactly the capacity and functionality needed when needed [5,14].…”
Section: Theoretical Framementioning
confidence: 99%
“…Several authors have worked at the identification of enablers of scalability and convertibility (see for example [6,[14][15][16]. Specifically, this paper relies on the observation that, being "reconfiguration" characteristics (i.e.…”
Section: Theoretical Framementioning
confidence: 99%
“…4.2 Managerial implications: the roadmap to implement reconfigurability Napoleone et al (2019) identified and classified the elements that enable convertibility and scalability, i.e. adaptability, to approximate reconfigurability-related concepts to practitioners.…”
Section: The Sequence Of Implementation Of the Core Characteristicsmentioning
confidence: 99%